Da ecologia à arquitetura da paisagem : os elementos naturais como recurso projetual para as estruturas urbanas na região hidrográfica entre Vitória e Serra (ES) - Baptista, Janaína Schmidel (2015)
This dissertation aims at reflecting on the role of natural elements in the spatial framework of contemporary cities in an approach grounded on principles of landscape ecology. The question to be answered is “How can urban structures play relevant roles t